(untitled) (Global Journal of Medical Research, 2016)
Melkersson-Rosenthal Syndrome is a rare entity of unknown etiology, characterized by the triad of symptoms: recurrent face and / or lip swelling, cracked or scrotal tongue and peripheral facial palsy. This symptomatology is often incomplete. It usually begins in childhood and relapses are common. We report a case of a patient with MRS followed in the ENT and Neck Surgery department of the University Hospital August 20th of Casablanca.